2018
DOI: 10.1242/bio.037390
|View full text |Cite
|
Sign up to set email alerts
|

The 17β-Estradiol induced upregulation of the Adhesion G-protein coupled receptor (ADGRG7) is modulated by ESRα and SP1 complex

Abstract: The physiological role and the regulation of ADGRG7 are not yet elucidated. The functional involvement of this receptor was linked with different physiological process such as reduced body weight, gastrointestinal function and recently, a gene variant in ADGRG7 was observed in patients with adolescent idiopathic scoliosis. Here, we identify the ADGRG7 as an estrogen-responsive gene under the regulation of estrogen receptor ERα in scoliotic osteoblasts and other cells lines. We found that ADGRG7 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Downregulation of EYA4 expression in cells of epithelial origin is consisting with its tumor suppressor function in these entities [61]. ADGRG7, alias GPR128, is a receptor of the adhesion GPCR family, whose functional relevance in thyroid lesions is virtually unknown; however, promoter studies indicated that ESRα and SP1 play a critical role in positively regulating expression of the receptor [62,63]. ACADL is a peroxisomal enzyme and is part of a family of enzymes known to be regulated by thyroid hormones [64].…”
Section: Downregulated Genes Of the 71 Deg Set From The Intersection mentioning
confidence: 99%
“…Downregulation of EYA4 expression in cells of epithelial origin is consisting with its tumor suppressor function in these entities [61]. ADGRG7, alias GPR128, is a receptor of the adhesion GPCR family, whose functional relevance in thyroid lesions is virtually unknown; however, promoter studies indicated that ESRα and SP1 play a critical role in positively regulating expression of the receptor [62,63]. ACADL is a peroxisomal enzyme and is part of a family of enzymes known to be regulated by thyroid hormones [64].…”
Section: Downregulated Genes Of the 71 Deg Set From The Intersection mentioning
confidence: 99%
“…Its overexpression, along with melatonin, enhances osteogenesis, whereas knockout of SPRY4 hampers osteogenesis in AIS patients ( 42 , 43 ). Low expression of ADGRG7 , GREM1 and GPR126 genes affects osteogenesis in AIS patients ( 44 47 ). CHD7 and BOC gene expression even positively correlated with bone mineral content in AIS patients ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study unraveled the upregulated adhesion G protein-coupled receptor G7 ADGRG7, with an unknown role in CRS. It is also unique to CRSwNP, and probably involved in cellular adhesion, an integral component of the plasma membrane [ 44 ]. B lymphocyte chemoattractant CXCL13 is upregulated only in CRSsNP, revealing a similar pattern as that indicated by Klingler et al for the T3 endotype [ 7 ].…”
Section: Discussionmentioning
confidence: 99%